Mobile phone ownership, digital technology use and acceptability of digital interventions among individuals on opioid use disorder treatment in Kenya - Kiburi, Sarah Kanana; Paruk, Saeeda; Chiliza, Bonginkosi (Frontiers in Digital Health, 2022)
Background There is limited research on the use of digital interventions among individuals with opioid use disorders (OUD) in low-and-middle income countries. This study aimed to assess mobile phone ownership, digital technology use and acceptability of digital interventions for treatment among individuals on treatment for OUD in Nairobi, Kenya. Methods A cross-sectional study was conducted among individuals with OUD. Structured questionnaires were used to collect data on socio-demographic and clinical characteristics, use of mobile phones and other digital technology and acceptability of digital interventions for treatment. Results One hundred and eighty participants were enrolled comprising 83.3% males with mean age of 31.5 years (SD 8.6). Mobile phone ownership was reported by 77.2% of participants of which 59.7% used smartphones. One hundred and sixty-six (92.2%) used phones to call, 82.8 and 77.2% used phones to send and receive text messages respectively; 30% used the internet; 57.2% had replaced the phone in past year and 51.1% of participants reported use of at least one social media platform, of these 44.4% had searched social media for information on drug use. Acceptability to receive treatment by phone was 95% and computer 49.4% with majority (88.1%) preferring a text message-based intervention. The preferred approach of delivery of a text message-based intervention were: one text message per day once a week, message to be personalized and individuals allowed to choose time and day to receive the message. Factors associated with acceptability of digital interventions were education level, being single, smartphone ownership and employment. Conclusion Majority of individuals on treatment for OUD had access to mobile phones but with high device turnover and limited access to computers and internet. There was high acceptability of digital interventions to provide treatment for OUDs, mostly through phones. These findings highlight factors to consider in the design of a digital intervention for this population.